(3hUGjG CejQ GdeDefjf jMji Hf MeRI hYghOg Edi ChdGOIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd Pi Gdef hGdEaVGd HYO aEf GdhdO deG cGf dg ehbY ai GdbdhH dGjNai s
(3BNQgG (B:s
(3hdcd efge fUjHg eeG jYde Efg eNGda JeJ GdhUGjG hGdMeO ddg Ydi cd MGd ef GdCMhGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
Keywords: (3abg GdePGgH GdCNQis